Design of a high efficiency and low power rectifier circuitry for piezoelectric generator - Wang, Mei (2015)
Nowadays green energy has become very popular and there has been a lot of research on battery-less technology for many wireless networks and biomedical implants. Harvesting energy from the surrounding environment is a possible way to deal with this problem. Piezoelectric energy harvesting has attracted many research interests. However, in such energy harvesting systems, interface circuits are required between the energy harvester and the output load, so as to supply power management functions. Therefore, this report focuses on interface circuits on voltage rectification and impedance matching for the piezoelectric energy harvester. This report presents the comparison between passive and active AC-DC rectifier, and the design of DC-DC Asynchronous buck-boost converter operating in discontinuous mode [DCM] for emulating maximum load impedance to achieve suboptimal impedance matching. These two circuits are separately implemented in advanced integrated circuit [IC] technology [Global Foundries 0.18um]. The DCM Asynchronous buck-boost converter manages to boost the lower input voltage to a fixed output voltage of 1.76V with the output ripple voltage of 15.6mV at the output capacitor of 1uF and the output resistor of 85k, thus achieving an efficiency of 67.77% with a load current of 21uA.